UPAYA MENINGKATKAN PEMAHAMAN SISWA PADA KONSEP STRUKTUR DAUN TUMBUHAN DAN FUNGSINYA SISWA MELALUI PENERAPAN MODEL INKUIRI TERBIMBING - Lukman Nulhakim (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
This research entitled Effort to Improve Student Understanding of Concepts in Materials Plant Leaf Structure and Function Through Application of Guided Inquiry in Elementary School fourth grade students Kadulimus 3. This study aims to improve students' understanding of concepts in science learning after using guided inkuri models and want to know the student activity using a model of guided inquiry. Methods This study uses classroom action research. This study was conducted with 2 cycles, each cycle consisting of 2 meetings and consists of four stages, namely: 1) planning, 2) action, 3) observations and 4) reflection. This study also used the instrument of observation and tests. Based on the research results obtained from tests students' understanding of the concept of mastery learning in the first cycle reached 68.29% and the second cycle increased to 87.80%. In addition to the student activity also is increased in the first cycle of 63.41% and 80.48% for the second cycle. Keyword : guided inquiry,learning outcomes, understanding of the concept